2021
DOI: 10.3390/nano11040840
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Gold Nanoparticles-Based Colorimetric Aptasensors for the Detection of Antibiotics: An Overview of the Past Decade

Abstract: Misuse of antibiotics has recently been considered a global issue because of its harmful effects on human health. Since conventional methods have numerous limitations, it is necessary to develop fast, simple, sensitive, and reproducible methods for the detection of antibiotics. Among numerous recently developed methods, aptasensors are fascinating because of their good specificity, sensitivity and selectivity. These kinds of biosensors combining aptamer with colorimetric applications of gold nanoparticles to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 115 publications
1
27
0
Order By: Relevance
“…A promising class of bioreceptors is DNA aptamers, which consist of short single-stranded oligonucleotides that provide high affinity and specificity for non-nucleotide molecules, including those with low molecular weight, toxic or nonimmunogenic [ 20 ]. The combination of AuNPs with aptamers in nanoaptasensors (NAS) is widely used to investigate the detection of a variety of analytes [ 21 , 22 , 23 , 24 ], with a growing number of reports addressing the detection of antibiotics in the field of food safety [ 25 , 26 ]. Surface plasmon resonance (SPR) is an optical property of AuNPs that allows the development of label-free NAS capable of analyzing multiple analytes in real time [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A promising class of bioreceptors is DNA aptamers, which consist of short single-stranded oligonucleotides that provide high affinity and specificity for non-nucleotide molecules, including those with low molecular weight, toxic or nonimmunogenic [ 20 ]. The combination of AuNPs with aptamers in nanoaptasensors (NAS) is widely used to investigate the detection of a variety of analytes [ 21 , 22 , 23 , 24 ], with a growing number of reports addressing the detection of antibiotics in the field of food safety [ 25 , 26 ]. Surface plasmon resonance (SPR) is an optical property of AuNPs that allows the development of label-free NAS capable of analyzing multiple analytes in real time [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The above example demonstrates how small molecules, while affordable and robust, do not provide a sufficient degree of selectivity for practical clinical use. Consequently, biologically derive constructs, such as antibodies, enzymes, and aptamers, have been explored as highly selective and sensitive bioreceptors (Zahra et al, 2021). For example, gold nanoparticles (AuNPs) were employed in conjunction with digoxin aptamers for the quantification of digoxin (Sarreshtehdar Emrani et al, 2015).…”
Section: Spectrophotometrymentioning
confidence: 99%
“…For example, aptamer wrapped AuNPs have been reported for the detection of T2-toxin in wheat and corn, 23 aflatoxins in milk, 24 , 25 and antibiotics in many food and environmental samples. 26 Recently, Zha et al reported a dual-modal immunosensor based on biotin-labeled IgG-modified AuNPs for the detection of chloroacetamide herbicides. 27 Also, sodium malonate capped AuNPs were reported for the detection of barium ions in gunshot residues as a potential application in forensic sciences.…”
Section: Introductionmentioning
confidence: 99%